The potential therapeutic applications and prognostic significance of metastasis associated in colon cancer 1 (MACC1) in cancers - Kopczyńska, Ewa Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2016)
The metastasis-associated in colon cancer-1 (MACC1) gene was identified in 2009. Expression of MACC1 was found to be significantly upregulated in primary and metastatic colon carcinomas compared to normal tissues or adenomas. The induction of MACC1 occurs at the crucial step of transition from a benign to a malignant phenotype. The aim of this review was to summarise current results of non-clinical and clinical studies on the role of MACC1 in the carcinogenesis and progression of cancer, as well its potential therapeutic and prognostic significance. The gene encoding the HGF receptor MET is a transcriptional target of MACC1. In addition to promoting the proliferation, invasion, and migration of colon cancer cells in cell culture and tumour growth and metastasis in mouse models, MACC1 also contributes to carcinogenesis and progression of colorectal cancer through the -catenin signalling pathway and mesenchymal-epithelial transition. MACC1 knockdown with si/sh RNA was investigated in cell lines of different types of cancer. MACC1 is a promising therapeutic target for antitumour and antimetastatic intervention strategies for cancers. Here, it is presented as a potential independent prognostic indicator of reduced overall survival as well as of the occurrence of distant metastasis in patients with different types of cancer.